Comparative analysis of the biological characteristics and mechanisms of azole resistance of clinical Aspergillus fumigatus strains - Zeng, Meng; Zhou, Xue; Yang, Chunhong; Liu, Yanfei; Zhang, Jinping; Xin, Caiyan; Qin, Gang; Liu, Fangyan; Song, Zhangyong (Frontiers in Microbiology, 2023)
Aspergillus fumigatus is a common causative pathogen of aspergillosis. At present, triazole resistance of A. fumigatus poses an important challenge to human health globally. In this study, the biological characteristics and mechanisms of azole resistance of five A. fumigatus strains (AF1, AF2, AF4, AF5, and AF8) were explored. There were notable differences in the sporulation and biofilm formation abilities of the five test strains as compared to the standard strain AF293. The ability of strain AF1 to avoid phagocytosis by MH-S cells was significantly decreased as compared to strain AF293, while that of strains AF2, AF4, and AF5 were significantly increased. Fungal burden analysis with Galleria mellonella larvae revealed differences in pathogenicity among the five strains. Moreover, the broth microdilution and E-test assays confirmed that strains AF1 and AF2 were resistant to itraconazole and isaconazole, while strains AF4, AF5, and AF8 were resistant to voriconazole and isaconazole. Strains AF1 and AF2 carried the cyp51A mutations TR34/L98H/V242I/S297T/F495I combined with the hmg1 mutation S541G, whereas strains AF4 and AF8 carried the cyp51A mutation TR46/Y121F/V242I/T289A, while strain AF5 had no cyp51A mutation. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis revealed differences in the expression levels of genes associated with ergosterol synthesis and efflux pumps among the five strains. In addition, transcriptomics, RT-qPCR, and the NAD + /NADH ratio demonstrated that the mechanism of voriconazole resistance of strain AF5 was related to overexpression of genes associated with energy production and efflux pumps. These findings will help to further elucidate the triazole resistance mechanism in A. fumigatus.